Calcaneal Ultrasound and Its Relation to Dietary and Lifestyle Factors, Anthropometry, and Vitamin D Deficiency in Young Medical Students - Jafri, Lena; Majid, Hafsa; Ahmed, Sibtain; Naureen, Ghazala; Khan, Aysha Habib (Frontiers in Endocrinology, 2021)
Background: Bone quality and peak bone mass are greatly affected by lifestyle factors. The objective of the study was to investigate the relationships between anthropometry, dietary and caloric intake, body composition measurements, physical activity, and vitamin D status with quantitative ultrasound-based bone parameters among medical students. Methods: Both male and female medical college students were included in this study. A detailed questionnaire was administered, collecting clinical, dietary, physical activity information, physical examination details, including body mass index (BMI). Body composition (total body fat, total body water, muscle mass, mean visceral fat mass, basal metabolic rate, bone mass using a bioelectrical impedance analyzer) and calcaneal heel ultrasound parameters were measured using an Osteosys Sonost-3000, Ultrasound Bone Densitometer were measured, respectively. Results: In this cross-sectional study, 211 healthy students with a mean age of 20.1 ± 1.1 years, 51.7 % (n=109) were males. Majority (79.4%) of the young adults had vitamin D deficiency. The mean BMI, calcium intake, and vitamin D levels were 22.35 ± 3.43 kg/m2, 788.7 ± 364.8 mg/day, and 15.02 ± 8.63 ng/ml, respectively. Female subjects compared to males had statistically significantly lower daily energy intake, muscle mass, visceral fat mass, calcium intake and vitamin D levels. In addition the median Z scores in females [-1.40 (-0.57to -1.82)] was significantly poorer than the male [-0.50(0.20 to -1.3)] counterparts, p-value <0.001. Multiple regression analysis showed that overall body fat percent (p-value 0.016) and visceral fat percent (p-value 0.029) were the only significant negative predictors to the calcaneal bone quality index (BQI) values. Conclusion: Adolescent lifestyle patterns can influence young adult bone strength. The young Pakistani females exhibited significantly lower dietary intakes and more inadequate bone parameters compared to males. Our data suggest that total body and visceral fat percent are the predominant negatively associated determinant of bone strength for this cohort. Calcaneal ultrasound can be utilized for mass screening of young adults for identification of low BMD.